Anal i s i s Yuridi s Terhadap Putusan No.5/Pid.Sus -Anak/2018/Pn.Mbn Terkait Anak Yang Melakukantindak Pidana Aborsi Akibat Korban Tindak Pidana Perkosaan - Diah Achriati Aulia; Emilda Firdaus; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The provisions of Article 75 and Article 194 of Law Number 36 Year 2009 concerning Health makeit clear that a person is prohibited from having an abortion unless there is an indication which endangersthe fetus and the mother. A person who has an abortion without the provisions of Article 75 will be subjectto imprisonment for a maximum of 10 years and a fine of Rp. 1,000,000,000.00 (one billion rupiah). But inthis case someone who has an abortion has an element of coercion or noodweer which means it cannot beconvicted. This case is an abortion resulting from rape by one of his own family members.In the verdict ofthe judge that the rape victim who had an abortion was sentenced to 6 months and 3 months of worktraining as well as paying the cost of the case, the rape victim as the abortionist is a daughter aged 15 yearsmeans that it is underage and not yet capable of law. The purpose of this thesis is: first, to find out theanalysis of the decision No.5 / Pid.Sus-Anak / 2018 / Pn.Mbn fulfill a sense of justice for children whocommit abortion due to victims of rape. Secondly, to find out the basis for the judge's judgment in rulingNo.5 / Pid.Sus-Anak / 2018 / Pn.Mbn to children who commit criminal acts of abortion due to rape victims.This research uses descriptive research with normative juridical approach while the data taken issecondary data so that the data collection is done by literature study. While the analysis of the data used inthis study is a qualitative analysis that examines the truth of the study of documentation and drawingconclusions from each Article by Article relating to the title of this study.The results showed that the criminal prosecution carried out by the Panel of Judges and the demandsof the Public Prosecutors were not appropriate, that a person convicted in this case was 15 (fifteen) yearsold and there was a nature of threats and force during his rape as a victim until he was pregnant. Whereasthere are irregularities in the court process which should be minors having special rights, the authorsanalyze Decision Number 5 / Pid. Sus-Anak / 2018 / PN. the girl.Keywords: Abortion, Rape Victim, Girls.